2012
DOI: 10.1371/journal.pone.0041344
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric Forms of Insulin Amyloid Aggregation Disrupt Outgrowth and Complexity of Neuron-Like PC12 Cells

Abstract: Formation of protein amyloid fibrils consists of a series of intermediates including oligomeric aggregates, proto-fibrillar structures, and finally mature fibrils. Recent studies show higher toxicity for oligomeric and proto-fibrillar intermediates of protein relative to their mature fibrils. Here the kinetic of the insulin amyloid fibrillation was evaluated using a variety of techniques including ThT fluorescence, Congo red absorbance, circular dichroism, and atomic force microscopy (AFM). The solution surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 54 publications
0
51
0
Order By: Relevance
“…Neuron-like PC12 cells have been widely studied as a model for neuronal cells [19][21]. In the current study, a 24 h H/SD resulted in an obvious apoptosis in the neuron-like PC12 cells.…”
Section: Resultsmentioning
confidence: 62%
“…Neuron-like PC12 cells have been widely studied as a model for neuronal cells [19][21]. In the current study, a 24 h H/SD resulted in an obvious apoptosis in the neuron-like PC12 cells.…”
Section: Resultsmentioning
confidence: 62%
“…On the other hand, early stage oligomers derived from the folded proteins such as insulin [100,101], SOD-1 [102], and acylphosphatase [103,104] largely preserved the native fold of these proteins. Formation of these early oligomers resembles the process of the surfactant micelle formation, although due to the required conformational changes in protein molecules, the oligomer formation process is much slower [105].…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques have been employed to study fibril formation including circular dichroism (CD), 14,15 transmission electron microscopy (TEM), 16 atomic force microscopy (AFM), 17 X-ray diffraction 18 and others. [19][20][21] CD spectroscopy studies showed that insulin adopts -helical conformations that can convert to appreciably -pleated structures as a function of time.…”
mentioning
confidence: 99%